Respuesta :

Answer:

-20/9

Step-by-step explanation:

you need to know that terms with negative exponents go into the denominator and then the exponent becomes positive

you also need to remember that, when dividing fractions, you multiply by the reciprocal

example:  ([tex]\frac{1}{5}[/tex])^-3 = 1/125

{(1/3)^-2 -(1/2)^-2 } / (1/4)^-2

simplify terms, one at a time:

(1/3)^-2  = (1/3)^2 = 1/9

(1/2)^-2  = (1/2)^2 = 1/4

(1/4)^-2 = (1/4)^2 =  1/16  

1/9 - 1/4 = 4/36 - 9/36 = -5/36

-5/36 ÷ 1/16 =  -5/36 · 16/1  =  -20/9